2011
DOI: 10.1136/hrt.2011.225656
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of the ACE inhibitor enalaprilat on the pulmonary, cerebral and systemic blood flow and resistance after the bidirectional cavopulmonary connection

Abstract: Enalaprilat did not increase total cardiac output but redistributed flow to the lower body, with a concomitant decrease in arterial oxygen saturation. It is difficult to increase cardiac output in patients with a BCPC and ACEI should be used with caution in those with borderline aortic saturations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In view of the importance of arterial pressure maintenance, the role of reducing R sys in improving CO is likely to be limited in Fontan patients. This is supported by previous clinical findings that ACEI did not significantly increase CO or improve exercise capacity in postoperative Fontan patients (39,44). Nevertheless, it has been speculated that reducing R sys using ACEI might be beneficial for patients with severe ventricular systolic dysfunction (68).…”
Section: Discussionsupporting
confidence: 77%
“…In view of the importance of arterial pressure maintenance, the role of reducing R sys in improving CO is likely to be limited in Fontan patients. This is supported by previous clinical findings that ACEI did not significantly increase CO or improve exercise capacity in postoperative Fontan patients (39,44). Nevertheless, it has been speculated that reducing R sys using ACEI might be beneficial for patients with severe ventricular systolic dysfunction (68).…”
Section: Discussionsupporting
confidence: 77%
“…It was reported that intravenous ACEI significantly decreased Qp/Qs in patients with BDG circulation, according to measurement of pulmonary and systemic blood flows. 15 It is suggested, in short, that a decrease in SVR by vasodilator administration may have resulted in a slight decrease in the proportion of SPCF of aortic blood flow in the present study compared with the published data.…”
Section: Spcf In Bdg Circulationsupporting
confidence: 72%
“…ACE inhibitors are often used in this complex circulation, but the effects of their vasodilatation are unclear. Work in children with bidirectional cavopulmonary shunts demonstrated that enalaprilat did not increase total cardiac output but redistributed flow to the lower body, with a concomitant decrease in arterial oxygen saturation 25. The authors concluded that it is difficult to increase cardiac output in these patients and ACE inhibitors should be used with caution in those with borderline aortic saturations.…”
Section: The Single Ventriclementioning
confidence: 97%